Cellular basis of host defence in pyelonephritis. III. Deletion of individual components. - Miller, T. E. (1987)
Hosts were depleted of individual cellular components to determine the effects of these manipulations on cellular defence mechanisms in acute and chronic pyelonephritis. T-lymphocytes were found to have little or no involvement in host protection but cyclosporin A administration had a dramatic effect on the gross pathology and bacteriological status of experimentally induced pyelonephritis. This change represented a major depression of host defence status. Cyclosporin A also activated resolved lesions in chronic pyelonephritis, associated with an increase in bacterial numbers. Administration of antineutrophil serum also led to a 1000-fold increase in bacterial numbers in the acute phase but had little effect on the host-parasite balance in chronic pyelonephritis. Macrophage blockade, on the other hand, did not affect the course of either acute or chronic infection. These studies have provided additional information on the immunobiology of experimental pyelonephritis and have focussed attention on the role of neutrophils, and an unidentified mechanism, affected by cyclosporin A, in host defence to renal infection.